LIδ18OSIO2 SYSTEMATICS IN VOLCANIC ROCKS AND MAFIC LOWER CRUSTAL GRANULITE XENOLITHS - Mengel K.; Hoefs J. (My University, 1990)
Liδ18OSiO2 relationships have been examined for suites of spilitized basaltic rocks (DSDP 504B; Xigaze Ophiolite; Blanco Fracture Zone; Greater Caucasus; Rhenohercynian Fold Belt) and intra-plate evolved tholeiites (Northern Hessian Depression and Vogelsberg, W Germany; Mount Falla, Transantarctic Mountains). Relative to unaltered MORB and intra-plate primary olivine tholeiites, both the spilitic rocks and the evolved tholeiites are characterized by Li and 18O enrichment. For the spilitic rocks, Li and 18O enrichment is accompanied by a loss of SiO2 as a result of seawater hydrothermal alteration, whereas the evolved tholeiites have gained SiO2, Li and 18O from fractionation of mafic phases and assimilation of crustal rocks.On Li vs. SiO2 and δ18O vs. SiO2 diagrams, the two rock groups plot largely in distinct fields, suggesting the possibility of so distinguishing between such lithologies in the ancient rock record. Mafic granulite xenoliths from the Northern Hessian Depression have elevated Li and 18O abundances at low SiO2 contents. Even after correction for extraction of felsic components, their Liδ18OSiO2 signatures plot within the field of spilitic protoliths, suggesting that the lower crust in this region contains relics of spilitic rocks from a former oceanic crust.